Peran Kepala Sekolah Dalam Pemberdayaan Komite Sekolah Di SMK Al-Asy’ari Komis Kedungdung Sampang - Badruttamam, Badruttamam; Husni, Ali (AL -ALLAM, 2025)
The school committee is an institution that plays a vital role in increasing the responsibility and role of the community in decision-making at school, as a provider of consideration in the implementation of educational policies, as a supporter, and as a controller. Therefore, the school committee needs to be empowered to be more effective in carrying out its duties and functions. This thesis discusses the role of the principal in empowering the school committee at SMK Al-Asy'ari Komis Kedungdung Sampang. There are three research focuses that are the main study in this study: First, What is the role of the principal in empowering the school committee at SMK Al-Asy'ari Komis? Second, How does the principal manage the empowerment of the school committee at SMK Al-Asy'ari Komis? Third, What are the obstacles faced by the principal in empowering the school committee at SMK Al-Asy'ari Komis? This study uses a descriptive qualitative approach. Data sources were obtained through observation, interviews, and documentation. The results of this study indicate that: the principal's role in empowering the school committee at SMK Al-Asy'ari Komis uses a participatory approach, also involving alumni, guardians, committee administrators, and the Islamic boarding school in all stages of the program. Monthly forums are used for communication and collaborative problem-solving with community input, so that the program belongs to all parties involved. The principal's management of the school committee empowerment at SMK Al-Asy'ari Komis is aspirational, but direct communication remains a barrier. The principal of SMK Al-Asy'ari Komis in empowering the school committee is the lack of activity of children who live far from their parents. Limited control and communication make it difficult to achieve learning quality standards.